Preparing for the demands of professional hockey - Neeld, K. (Strength and Conditioning Journal, 2018)
Preparing players for the rigors of a professional ice hockey season requires a thorough understanding of the physical demands and injury patterns of the sport. This article combines an analysis of biomechanical and energy system demands with a review of the most prominent injuries to propose a comprehensive assessment battery for hockey players. Concepts from multiple periodization models are integrated to present an annual plan, including specific programming strategies for the development of speed, strength, and repeat sprint ability. Sample training plans are used to illustrate the application of the discussed principles, serving to maximize both performance and durability.Increasing balance stability during high-intensity athletic performance has been shown to be critical in sport performance. Previous research shows that balance training programs may be beneficial in rehabilitation and prevention of musculoskeletal injuries. There are several ways to test balance performance and implement balance training. However, with greater incidence of musculoskeletal injuries in women and with modest conclusive literature in female athletes' balance assessment and training, there is a need for easy understanding and application of these concepts. Therefore, this article provides coaches and practitioners with a short review of the literature on balance in female athletes.